2018
DOI: 10.1029/2017ja024980
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Equatorial and Low‐Latitude Plasma Irregularities as Investigated Using a Meridional Chain of Radio Experiments Over India

Abstract: The characteristics of equatorial and low-latitude plasma irregularities are studied using a meridional chain of ionosondes located at Tirunelveli, Hyderabad, and Allahabad and Global Positioning System (GPS) receivers located at Tirunelveli, Mumbai, and Nagpur during the year 2015. The observations suggest that while stronger and longer duration of equatorial spread F irregularities occur in the postsunset sector during equinoxes and winter, they occur mostly in the postmidnight sector during summer, while be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 43 publications
2
7
0
Order By: Relevance
“…Statistical and case 55 studies were successful in describing the occurrence features of the irregularity with local time, seasonal variations, solar cycle and its geographical dependence. They confirm already existing observational characteristics of the irregularity and give new insights into its global distribution scenarios (Otsuka et al, 2006, Nishoka et al, 2008Sripathi et al, 2018). Nevertheless, systematic research of the ionospheric irregularity with ROTI is lacking at specific area for varying solar 60 activity.…”
Section: Introductionsupporting
confidence: 76%
See 1 more Smart Citation
“…Statistical and case 55 studies were successful in describing the occurrence features of the irregularity with local time, seasonal variations, solar cycle and its geographical dependence. They confirm already existing observational characteristics of the irregularity and give new insights into its global distribution scenarios (Otsuka et al, 2006, Nishoka et al, 2008Sripathi et al, 2018). Nevertheless, systematic research of the ionospheric irregularity with ROTI is lacking at specific area for varying solar 60 activity.…”
Section: Introductionsupporting
confidence: 76%
“…equatorial spread F mostly occurred in equinoxes and winter. Further the postmidnight spread F during summer is found to be stronger and earlier at low latitudes followed by their occurrence at the equator (Sripathi et al, 2018). 280 Figure 4 shows the variation of the irregularity's strength generally complies with its LOR in Taoyuan, although a one-to-one correspondence does not exist coming to those of latitude belt.…”
Section: Discussionmentioning
confidence: 94%
“…The TEC itself depends on the activity of the sunspot, seasonal, diurnal and spatial variations and the line of sight that includes knowledge of the satellite's elevation and azimuth [26]. The TEC may be calculated as [18], [22], [27]: The rate of change of the total electron content (ROT), calculated from the differential carrier phase, may provide information on large scale electron density irregularities. While the ROT can be deterred as the equation below [22]:…”
Section: Instrumentation and Data Collectionmentioning
confidence: 99%
“…In this study, a total of 73 moderate to intense geomagnetic storm events are identified and classified them into three categories according to Aarons (1991) criteria, which is commonly accepted criteria to explore the occurrence of ionospheric irregularities. It is believed that low-latitude Es layers may be modified due to modified winds/electric fields during the geomagnetic storms, and hence, examining their role in the generation of ESF irregularities is very important (e.g., Li et al, 2006;Sripathi et al, 2018). (2) Category II: if the maximum negative of Dst occurs during the midnight-down (at 00:00-06:00 LT), the height of the ionospheric F layer first rises and then falls, which generated the ionospheric irregularities.…”
Section: Introductionmentioning
confidence: 99%
“…As the E region at Hyderabad is connected to the base of the F region at 250 km at magnetic equator, any changes in the E ‐region density can have significant impact on the ESF irregularities as field‐integrated conductivity plays important role in deciding the growth of the plasma irregularities. It is believed that low‐latitude Es layers may be modified due to modified winds/electric fields during the geomagnetic storms, and hence, examining their role in the generation of ESF irregularities is very important (e.g., Li et al, ; Sripathi et al, ). The study also investigates the seasonal response of early morning height rise and their relation to occurrence of ionospheric irregularities during the disturbed conditions.…”
Section: Introductionmentioning
confidence: 99%